Centralizing fieldwork : critical perspectives from primatology, biological, and social anthropology - MacClancy, Jeremy; Fuentes, Agustin (Studies of the Biosocial Society, 2011)
Fieldwork is a central method of research throughout anthropology, a much-valued, much-vaunted mode of generating information. But its nature and process have been seriously understudied in biological anthropology and primatology. This comparative investigation looks critically at this research practice.